Fifty years of the Divorce Reform Act 1969 - Probert, Rebecca; Monk, Daniel; Miles, Joanna (London [England] : Hart Publishing, 2022)
"The enactment of the Divorce Reform Act 1969 was a landmark moment in family law. Coming into force in 1971, it had a significant impact on legal practice and was followed by a dramatic increase in divorce rates, reflecting changes in social attitudes. This new interdisciplinary collection explores the background to the 1969 Act and its influence on law and society. Bringing together scholars from law, sociology, history, demography, and film and literature, it reflects on the changes to divorce law and practice over the past 50 years, and the changing impact of divorce on different people in society, particularly women. As such, it offers a 'biography' of this important piece of legislation, moving from its conception and birth, through its reception and development, to its imminent demise. Looking to the future, and to the new law introduced by the Divorce, Dissolution and Separation Act 2020, this collection suggests ways for evaluating what makes a 'good' divorce law. This brilliant collection gives insight not only into this crucial piece of legislation, but also into a key period of societal change."--
Foreword / Lady Hale -- PART ONE -- INTRODUCTION -- 1. 'Irretrievably Broken'? Introducing the Life-Story of the Divorce Reform Act 1969 / Joanna Miles, Daniel Monk and Rebecca Probert -- 2. Divorces by Fact Proven Over the Past Half Century in England and Wales: The Historical Context, Statistical Trends and Future Prospects / John Haskey -- PART TWO -- BACKGROUND -- 3. Dynamic Impasse: Divorce and British Film in the Mid-Twentieth Century / James Brown -- 4. Feminism, Property and Divorce Law Reform in the 1960s / Rosemary Auchmuty -- 5. Putting Asunder - Reappraised / Rosie Sinclair -- 6. Behind Casanova's Charter: Edith Summerskill, Divorce and the Deserted Wife / Sharon Thompson -- PART THREE -- TELLING STORIES ABOUT DIVORCE AND MARRIAGE -- 7. Divorced from Reality? Literary Depictions of the Legal Process for Ending a Marriage, 1971-2021 / Rebecca Probert -- 8. Judging Matrimonial Behaviour / Joanna Miles -- 9. Telling Tales? Establishing Irretrievable Breakdown under the Matrimonial Causes Act 1973 / Liz Trinder -- 10. Royal Divorces and the Remaking of Marriage and Monarchy / Daniel Monk -- PART FOUR -- CONTEMPORARY PERSPECTIVES AND CHALLENGES -- 11. Divorced from Human Rights? English Divorce Law under Human Rights Scrutiny / Carmen Draghici -- 12. British Muslim Communities, Islamic Divorce and English Family Law / Samia Bano -- 13. Dissolution, Divorce and Changing Practices of Commitment / Brian Heaphy and James Hodgson -- Afterword / John Eekelaar
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily.
Mode of access: World Wide Web.
Keywords: Great Britain; Divorce -- Law and legislation -- Great Britain -- History; Law reform -- Great Britain -- History; Electronic books